The role of interleukins in peripheral nerve injury and the current status of treatment - Shen, Yue; Li, MingZhu; Jin, ShengBo; Yu, ZiYang; Liu, Qian; Yao, HuiNi; Jiang, YuXin; Fu, JiaQing; Li, NingXin (Frontiers in Immunology, 2026)
Peripheral Nerve Injury (PNI) is a common condition in modern clinical practice, characterized by a high incidence and significant debilitating consequences. This narrative review systematically delineates the dual functions of key pro-inflammatory (e.g., IL-1β, IL-6, IL-17) and anti-inflammatory (e.g., IL-4, IL-10, IL-13) interleukins in the spatiotemporal context of nerve injury. This is a narrative review, the review systematically summarizes the dual pro-inflammatory and anti-inflammatory roles of interleukins in peripheral nerve injury. The therapeutic potential of interleukin-based treatment strategies, including inhibitors, agonists, and their combined applications with cell therapy, gene therapy, physical therapy, etc., was explored, and the limitations of current research and future research directions were pointed out. By synthesizing current evidence, this review aims to provide a comprehensive mechanistic overview and highlight emerging interleukin-centric therapeutic paradigms for PNI.